The Influence of Cafe Atmosphere and Word of Mouth on Purchasing Decisions: The Role of Brand Image as a Mediating Variable - Benamen , Masna; Asnawi, Aisah; Huwae, Victor E. (Jurnal Ekonomi, 2024)
This research aims to analyze the influence of cafe atmosphere and word of mouth on visiting decisions mediated by brand image. This research is quantitative descriptive research. The population in this study were Gospel Cafe visitors. The sample in this study was 190 respondents. By using a questionnaire, sampling for this research aims a non-probability sampling technique with a purposive sampling method. The data analysis method used is SEM PLS to test the formative and reflective models between indicators. Based on the results of data tests that have been carried out, it shows that the cafe atmosphere variable (X1) has a positive and significant influence on the brand image (Y) as a mediating variable and purchasing decision variable (Z). , word of mouth (X2) has a positive and significant influence on brand image (Y) as well as a mediating variable and purchasing decision variable (Z). The research results also show that word of mouth has a very high influence on brand image and visiting decisions. This shows that the decision to visit a cafe and the image formed are still dominated by offline promotional factors or references from other people who have visited before.